(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper attempts to compare dental images (grayscale/truecolor) degraded with blur and noise using different de-blurring filters. The image is degraded by the combination of Gaussian/Average blur and Salt & Pepper /Speckle / Poisson / Gaussian noise for different values of PSF. All the degraded images are then restored using Wiener Filter, Lucy Richardson Filter technique. Restoration by Wiener filter takes place for different values of estimated NSR and restoration by Lucy-Richardson for different iterations. The restored images are then compared on the basis of SNR, MSE and PSNR values. This comparison are made to find which filter technique removes which combination of blur and noise on what value of PSF with high PSNR/SNR and low MSE value.